Influence of size reduction of crosslinked rubber particles on phase interface in dynamically vulcanized poly (vinylidene fluoride)/silicone rubber blends. (October 2017) - Chen, Yukun; Fan, Jianfeng; Wang, Wentao; Wang, Yanpeng; Xu, Chuanhui; Yuan, Daosheng
Abstract: In this paper, the influence of rubber particle size on the phase interface in dynamically vulcanized poly(vinylidene fluoride)/silicone rubber (PVDF/SR) blends without any modifier is discussed through the studies of specific surface of crosslinked SR particles, crystallization behavior and crystal morphology of the PVDF phase, interfacial crystallization, melt rheological behavior and mechanical properties of blends. A series of decreased average particle size was successfully obtained by control of rotor rate. It was found that properly high rotor rate helped to achieve a reduced particle size and a narrowing size distribution. The reduced SR particle size enlarged the PVDF/SR interface which has a positive effect on the interfacial crystallization and the melt rheological behavior. At high SR content, the negative effect of the poor interface interactions played the dominate role on determining the mechanical properties. However, the blend exhibited a unique stiffness-toughness balance at the PVDF/SR = 90/10. We hope that the present study could help to lay a scientific foundation for further design of a useful PVDF/SR blend with promoted properties to partly replace the high-cost synthetic fluorosilicone materials.